2007
DOI: 10.1007/s00425-007-0645-5
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric vapor pressure deficit is critical in predicting growth response of “cool-season” grass Festuca arundinacea to temperature change

Abstract: There is a lack of information on plant response to multifactor environmental variability including the interactive response to temperature and atmospheric humidity. These two factors are almost always confounded because saturated vapor pressure increases exponentially with temperature, and vapor pressure deficit (VPD) could have a large impact on plant growth. In this study using climate controlled mini-greenhouses, we examined the interacting influence of temperature and VPD on long-term growth of tall fescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Our results for lucerne are similar to studies that suggested an optimum temperature for growth between 15-25 • C in the daytime and 10-20 • C in the night-time [14,89,91], but contrasts with studies showing no reduction in growth between 10-30 • C, with marked reductions being observed only at temperatures around 40 • C [92,102,103]. Previous studies on tall fescue have observed similar trends with festucoid species observed to have an optimum growth temperature between 20-27 • C [85,87,104,105]. The significant declines in biomass for tall fescue, despite little change in photosynthetic capacity, suggests that whole-plant productivity may be more sink-limited than source-limited [106], with productivity regulated by tiller production & leaf canopy orientation [107].…”
Section: Discussionmentioning
confidence: 71%
“…Our results for lucerne are similar to studies that suggested an optimum temperature for growth between 15-25 • C in the daytime and 10-20 • C in the night-time [14,89,91], but contrasts with studies showing no reduction in growth between 10-30 • C, with marked reductions being observed only at temperatures around 40 • C [92,102,103]. Previous studies on tall fescue have observed similar trends with festucoid species observed to have an optimum growth temperature between 20-27 • C [85,87,104,105]. The significant declines in biomass for tall fescue, despite little change in photosynthetic capacity, suggests that whole-plant productivity may be more sink-limited than source-limited [106], with productivity regulated by tiller production & leaf canopy orientation [107].…”
Section: Discussionmentioning
confidence: 71%
“…In agricultural systems, the control of water loss in crop plants affects their water use strategy and can affect the seasonal water budget; conservation of water early in the season can leave water for growth during drier parts of the season (Sinclair et al . ). In natural ecosystems, high K root (independent of other root characteristics, Table ) may provide a competitive advantage for water uptake in grasses, as these plants would avoid the large midday depression in carbon assimilation that often results from high vapor pressure deficit.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of both RH and variation in temperature is combined by the VPD, which indicates the change between the saturated vapor pressure (inside the stomatal cavity) and actual air vapor pressure (surrounding environment) (Fanourakis et al, 2016). Research has shown that VPD not only has a direct effect on stomatal conductance (g s ), photosynthesis, and water transport (Sinclair et al, 2007) but also affects plant temperature via transpiration. Greater VPD reduced leaf temperature by stimulating transpiration (Fanourakis et al,2015).…”
mentioning
confidence: 99%